2018
DOI: 10.26582/k.50.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Are team sport games more motivating than individual exercise for middle-aged women?

Abstract: Abstract:The aim of this study was to investigate the levels of motivation associated with the participation in floorball (indoor hockey) and spinning, and how these levels of motivation predicted continuation. A sample of 66 middle-aged women participated in a 12-week intervention of either floorball or spinning. They filled out the Sport Motivation Scale in week 2 and week 11 of the intervention, and data was also collected on their continuation six and 12 months after the intervention. A repeated measures M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…Hypothesis 2b. Elite athletes and athletes practicing team sports would display higher intrinsic motivation toward PA compared to non-elite athletes and athletes in individual sports, respectively, as shown in non-pandemic studies (Nielsen and Wikman, 2018;Hendry et al, 2019;Moradi et al, 2020); team athletes would also report lower body dissatisfaction compared to individual ones (Kristjánsdóttir et al, 2019).…”
Section: The Present Studymentioning
confidence: 87%
“…Hypothesis 2b. Elite athletes and athletes practicing team sports would display higher intrinsic motivation toward PA compared to non-elite athletes and athletes in individual sports, respectively, as shown in non-pandemic studies (Nielsen and Wikman, 2018;Hendry et al, 2019;Moradi et al, 2020); team athletes would also report lower body dissatisfaction compared to individual ones (Kristjánsdóttir et al, 2019).…”
Section: The Present Studymentioning
confidence: 87%
“…Sports games have various forms and are very interesting, which can arouse students' learning enthusiasm and promote the concentration of attention. Wikman, et al [27] revealed the importance of motivation for persistence by taking cricket as the research object, and found that the group with motivation intervention had higher intrinsic motivation and higher extrinsic motivation of self-determination. In view of the impact of educational gamification on students' learning motivation, Chapman and Rich [28] investigated the role of gamification curriculum in stimulating students' overall motivation through a cognitive survey.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto la sensación de autonomía como la de competencia son dos de las necesidades psicológicas básicas que influyen en la práctica de actividad físico-deportiva (Carrasco et al, 2019), y como se ha visto en este estudio es posible que se puedan satisfacer en mayor medida a través de la práctica del deporte individual y en concreto mediante el deporte de orientación. Aunque sin embargo, en otras investigaciones se ha demostrado que los practicantes de deportes colectivos presentaban unos valores superiores de satisfacción de las necesidades psicológicas básicas que aquellos que practicaban un deporte individual (Ferreira et al, 2018;Lamoneda y Huertas-Delgado, 2019), pero sobre todo en cuanto a la variable de relación (Wikman et al, 2018) que proporciona un ambiente de aprendizaje que facilita las interacciones interpersonales y que el alumnado se integre; y la variable de competencia (Hellín et al, 2007) donde cada estudiante pueda completar las actividades en base a su nivel motriz. Por lo tanto, cada deporte que se trabaje en una unidad didáctica tiene unas aportaciones diferentes a la hora de satisfacer las necesidades psicológicas básicas, por lo que parece oportuno hacer énfasis en los contenidos en los que se pueda trabajar mejor las tres necesidades y también sería conveniente que se tengan en cuenta a la hora de diseñar las actividades, diseñando ejercicios para trabajar la competencia, donde las tareas se ajusten al nivel motriz del alumnado; llevando a cabo estrategias de aprendizaje cooperativo para fomentar la relación y otorgando capacidad de decisión a los alumnos no solo en las actividades sino eligiendo contenidos, espacios o materiales.…”
Section: Discussionunclassified
“…La orientación deportiva es una modalidad donde la parte cognitiva es muy importante y donde los factores psicológicos pueden interferir en el proceso de cognición e incluso en el factor físico (Viñambres, 2008). En cuanto al floorball encontramos estudios que muestran una mayor motivación intrínseca a través de la práctica de este deporte (Wikman et al, 2018).…”
Section: Introductionunclassified